David Henry Hwang's Dramatization of the concept of ethnicity : A semiotic study of three selected plays - Walaa Mostafa Abdelazeem Hassan; Mona Ahmed Elhalawany (Cairo : Walaa Mostafa Abdelazeem Hassan, 2019)
The thesis in question tackles David Henry Hwang's skillful dramatization of the concept of ethnicity. He depicts the struggle for existence and the long suffering of the Chinese minority in the ethnic American society. Hwang also tackles the conflict between the Western and the Eastern cultures shedding light on the entrapment between the two cultures and the relationship between the self and the other. The thesis aims at focusing on Hwang's portrayal of cultural differences in a multicultural society. The Chinese's question of ethnic identity, assimilation and their failure to cope with the American way of life are perfectly brought to focus. The critical methodology of the dissertation follows Martin Esslin's vision of the semiotics of the dramatic text which aims to decode the multiple dramatic layers of meaning in an attempt to convey the playwright's signifying world
Thesis (M.A) - Cairo University - Faculty of Arts - Department of English
Issued also as CD
Keywords: Chinese minority; Chinese-American drama; Ethnicity